THEORETICAL APPROACH OF EVALUATION & ASSESSMENT WITHIN EDUCATIONAL CONTEXT - Zacharis, Konstantinos Vasileios (Advances in Social Sciences Research Journal, 2019)
Modern management systems incorporate evaluation and self-assessment mechanisms to improve the quality of services and to enhance their added value in terms of the taxes spent on their operation. The same applies to the public sector educational systems at all levels (primary, secondary, tertiary). Within this context, the objectives of the professional teachers, which are complex and complex, are analyzed. They include not only the knowledge transfer but also instilling values and attitudes to pupils. This is why most teachers believe it is not a morally good idea to try to evaluate these "sensitive" systems. Thus, any legislative actions on evaluation causes intense controversy and concern in the public dialogue since it is de facto considered non-democratic and contrary to the cultural ethics of the profession of teachers. Under these circumstances, the Ministry of Education decided to apply the evaluation in two parallel steps, internal and external. In this paper we look at the effectiveness and efficiency of this strategy, along with the policies that are in place for that purpose.